The Effect of Murottal Therapy on Blood Pressure in Elderly Patients With Hypertension at Jambidan Posyandu, Banguntapan 1 Community Health Center - Arita Muwarni; Sarni Anggoro (JOURNAL OF NONCOMMUNICABLE DISEASES, 2023)
Hypertension is a non-communicable disease that poses a threat to people in developing countries. Hypertension is a cause of death, called the silent killer, and is mostly suffered by the elderly. This is caused by physiological factors, namely decreased body function due to the aging process, so that non-communicable diseases attack many elderly people. The global health standard does not only rely on curative measures because most diseases can be prevented by healthy lifestyles and avoiding risky lifestyles. This study aims to determine the effect of murottal therapy on blood pressure in the elderly with hypertension. This study used a quasi-experimental research design using a one-group pre-post test design and a sample size of 34 elderly with the sampling technique of purposive sampling and bivariate analysis using the Wilcoxon test. The result is that murottal therapy has an effect on reducing blood pressure in elderly people with hypertension, with a Wilcoxon signed rank test p-value of 0.000 (PÂ <0.05), so there is an effect of murottal therapy on blood pressure in the elderly with hypertension.